FOLFIRINOX as First-Line Treatment for Unresectable Acinar Cell Carcinoma of the Pancreas: A Case Report - Schempf, U.; Sipos, B.; König, C.; Malek, N. P.; Bitzer, M.; Plentz, R. R. (Zeitschrift für Gastroenterologie, 2014)
Pancreatic acinar cell carcinoma (ACC) is a rare, aggressive variant of pancreatic ductal adenocarcinoma. Surgery is the only curative treatment option and protocols for palliative chemotherapies in this context are not standardized yet. We reported a 63-year-old white male patient who had painless jaundice, weight loss, elevated bilirubin, and a mass of the pancreatic head as well as liver metastasis. Core biopsy revealed the diagnosis of ACC. Therapy with FOLFIRINOX resulted in a significant decrease of the primary tumor and regressiveness of a liver metastasis after chemotherapy. Our report suggests that pancreatic ACC treated by FOLFIRINOX is well tolerated and might be superior to other single chemotherapies in this rare tumor disease.
Keywords: Azinuszellkarzinom (ACC); FOLFIRINOX; Pankreas